Analysis of the Relationship between Neutrophils, Lymphocytes, and Comorbidities with Time to Death in COVID-19 Patients - Hendra Tanuwijaya; Susanthy Djajalaksana; Rezki Tantular (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND: COVID-19 caused 5.4 million deaths in 2021. Various parameters such as comorbidities and laboratory findings are known to be predictors of death in COVID-19, but these findings differ in each country, and their relationship to time of death has not been widely studied. This study was conducted to determine the relationship between levels of neutrophils, lymphocytes, neutrophil to lymphocyte ratio (NLR), and comorbidities with time to death in COVID-19. METHODS: A retrospective cohort study was conducted from April 2020 to September 2021 in the COVID-19 Inpatient Room at RSUD dr. Saiful Anwar Malang with 300 COVID-19 patient subjects aged 18 years and over. Data on comorbidities (hypertension, CAD, HF, obesity, COPD, CKD, cancer), time to death, and laboratory were taken from medical records. The Kolmogorov-Smirnov test, Chi square test and Mann Whitney test were carried out to analyze the data. RESULTS: There was a significant relationship between neutrophil levels and time to death, as well as a significant difference in neutrophil levels in the group with time to death >48 hours with comorbidities compared to <48 hours with and without comorbidities. There was a significant difference in lymphocyte levels and NLR in patients with comorbidities with time to death <48 hours and >48 hours (p < 0.05). CONCLUSION: There is a significant relationship between neutrophil levels and time to death, both in subjects with and without comorbidities showing the potential of neutrophil levels as a predictor of time to death in COVID-19.